Automated Verbalization of ORM Models in Malay and Mandarin - Lim, Shin Huei; Halpin, Terry (IGI Global, 2016)
Fact-oriented modeling approaches such as Object-Role Modeling (ORM) include a rich graphical notation for capturing business constraints, allowing modelers to visualize fine details of their data models. These data models should be validated with domain experts who best understand the business requirements, even if unfamiliar with the graphical notation. Hence, the data models are best validated by verbalizing the models in a controlled natural language, and by populating the relevant fact types with examples. Comparatively little support exists for verbalizing fact-based models in non-English languages, especially Asian languages. This paper describes the authors' work on verbalizing ORM models in Bahasa Melayu (Malay) and Mandarin. The authors specify some typical transformation patterns, discuss features of these languages requiring special treatment (e.g. noun classifiers, repositioning of modal operators, and different uses for terms equivalent to “who” and “that” in English), and describe their current implementation efforts.